A Family of Homologous Heterospin Complexes Based on Lanthanides and Biradical Ligands. Issue 24 (25th June 2013) - Tian, Li; Sun, Ya‐Qiu; Na, Bo; Cheng, Peng
Abstract: Four complexes based on rare earth biradicals [Ln(hfac)3 (NITPh m bis)2 ]2 {Ln = La (1 ), Nd (2 ), Gd (3 ), Tb (4 ); hfac = hexafluoroacetylacetone; NITPh m bis = [1, 3‐bis(1′‐oxyl‐3′‐oxido‐4′, 4′, 5′, 5′‐tetramethyl‐4, 5‐hydro‐1 H ‐imidazol‐2‐yl)benzene]} were successfully synthesized under appropriate conditions. Single‐crystal structures show that1 is a mononuclear two spin complex and2 –4 are mononuclear three spin complexes, in which a NITPh m bis molecule acts as a bidentate ligand with one coordinated lanthanide ion. The four complexes are isomorphous, the coordination number around the lanthanide ion is eight, and the polyhedron is a 4, 4‐bicappped trigonal prism. For lanthanum(III) complex1, the temperature dependence of the magnetic susceptibility indicates that weakly antiferromagnetically coupled radicals exist ( J rad–rad = –1.2 cm –1 ). In the case of neodymium(III) complex2, its magnetic behavior gives antiferromagnetic Nd III –radical interactions, whereas for complexes3 and4, static magnetic properties show that the Gd III and Tb III ions interact ferromagnetically with the radical. The dynamic magnetic properties of4 were also measured, and4 was found to exhibit slow relaxation of the magnetization at low temperature. Abstract : Four mononuclear multispin complexes based on rare earth biradicals were synthesized. The Ln–organic radical interaction is antiferromagnetic for light rare earth metals, whereas this interaction is ferromagnetic for heavy rare earth metals. Dynamic magnetic properties were measured for the Tb III complex, and slow relaxation of the magnetization at low temperature was observed.